1988
DOI: 10.1159/000185057
|View full text |Cite
|
Sign up to set email alerts
|

On the Mechanism of Toluene-Induced Renal Tubular Acidosis

Abstract: This study was aimed to investigate the pathogenesis of toluene-induced renal tubular acidosis (RTA). In 5 individuals addicted to toluene sniffing we documented the occurrence of hypokalemia and hyperchloremic metabolic acidosis associated with inability to lower urine pH below 5.5 (6.06 ± 0.24). Overall kidney bicarbonate reabsorption was normal or enhanced, a feature characteristic of the distal form of RTA (DRTA). These findings resemble those found during the administration of amphotericin B, a drug felt … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…The mechanism involved is an inability of the distal tubule to excrete hydrogen ions as ammonium. This defect in distal acidification could be mediated by decreased proton conductance through the active conduction pathway (Batlle et al, 1988). However, other authors have suggested that overproduction of hippuric acid by toluene metabolism also contributes to acidosis in toluene poisoning (Carlisle et al, 1991), and could explain the finding of high anion gaps in the other 12 patients in this series.…”
Section: Discussionmentioning
confidence: 60%
“…The mechanism involved is an inability of the distal tubule to excrete hydrogen ions as ammonium. This defect in distal acidification could be mediated by decreased proton conductance through the active conduction pathway (Batlle et al, 1988). However, other authors have suggested that overproduction of hippuric acid by toluene metabolism also contributes to acidosis in toluene poisoning (Carlisle et al, 1991), and could explain the finding of high anion gaps in the other 12 patients in this series.…”
Section: Discussionmentioning
confidence: 60%
“…It can be speculated that decreased immunoreactivity of pendrin in the collecting duct plays a compensatory role, acting to decrease the secretion of HCO3 -and prevent the development of acidosis, but the change is not able to fully compensate for the acidosis (thus, H + -ATPase might play a key role). Patients with secondary distal RTA require a diagnostic work-up to determine the etiology, which can include such drugs as ifosfamide, amphotericin B, or lithium, hypercalciuric conditions, medullary sponge kidney, nephrocalcinosis, obstructive uropathy and autoimmune diseases, including Sjögren's syndrome (2,(9)(10)(11). Distal RTA occurs in up to 25% of patients with Sjögren's syndrome (12).…”
Section: Discussionmentioning
confidence: 99%
“…There are studies reporting hepatic, renal, cardiovascular, and hemopoietic system damages in thinner addicts. 1,6,14,15 In a study conducted in 2000, two types of rats were exposed to inhalation of 2-butoxyethanol chemical which is also present in thinner, for defined periods every day for 14 weeks and 2 years, respectively. At the end of the period in the kidneys of the sacrificed subjects, renal tubular degeneration and increase in hemosiderin pigmentation were detected.…”
Section: Discussionmentioning
confidence: 99%
“…In some of them, besides renal tubular acidosis, aminoaciduria, hypophosphoremia, and hypocalcemia had developed. 15 In a case report by Erramouspe et al, it was established that the infant of a mother who has smelled dye thinner containing toluene during her pregnancy was born with renal tubular acidosis. 16 The reason for renal toxicity due to smelling of adhesives seems to be toluene.…”
Section: Discussionmentioning
confidence: 99%